1998
DOI: 10.1083/jcb.141.2.419
|View full text |Cite
|
Sign up to set email alerts
|

Image Reconstructions of Microtubules Decorated with Monomeric and Dimeric Kinesins: Comparison with X-Ray Structure and Implications for Motility

Abstract: We have decorated microtubules with monomeric and dimeric kinesin constructs, studied their structure by cryoelectron microscopy and three-dimensional image reconstruction, and compared the results with the x-ray crystal structure of monomeric and dimeric kinesin. A monomeric kinesin construct (rK354, containing only a short neck helix insufficient for coiled-coil formation) decorates microtubules with a stoichiometry of one kinesin head per tubulin subunit (α–β-heterodimer). The orientation of the kinesin hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
105
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 78 publications
17
105
2
Order By: Relevance
“…Although subsequent studies gave equivalent results for dimeric ncd (Arnal et al, 1996;Sosa et al, 1997), there has been disagreement over dimeric kinesin. The results of Arnal et al (1996) were similar to ours, but the structures obtained by Hoenger et al (1998) showed no additional density compared with the monomeric structure. The latter group have suggested this was because each head of a dimer was bound to separate sites on tubulin.…”
Section: Introductionsupporting
confidence: 86%
See 4 more Smart Citations
“…Although subsequent studies gave equivalent results for dimeric ncd (Arnal et al, 1996;Sosa et al, 1997), there has been disagreement over dimeric kinesin. The results of Arnal et al (1996) were similar to ours, but the structures obtained by Hoenger et al (1998) showed no additional density compared with the monomeric structure. The latter group have suggested this was because each head of a dimer was bound to separate sites on tubulin.…”
Section: Introductionsupporting
confidence: 86%
“…Similar predictions were reported by Sosa et al (1997), in orienting the monomeric ncd⅐ADP crystal structure into a map of ncd complexed to microtubules in the presence of AMP⅐PNP, and by Hoenger et al (1998), in docking the kinesin⅐ADP crystal structure into a map showing kinesin in the same state. The orientation of the directly bound heads appeared to be in agreement with most of the data obtained by biochemical and mutagenesis studies (Yang et al, 1989;Woehlke et al, 1997;Alonso et al, 1998).…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations